Heart Rate Variability Is Associated with Survival in Patients with Brain Metastasis: A Preliminary Report. (12th September 2013) - Wang, Yu-Ming; Wu, Hau-Tieng; Huang, Eng-Yen; Kou, Yu Ru; Hseu, Shu-Shya
Abstract : Impaired heart rate variability (HRV) has been demonstrated as a negative survival prognosticator in various diseases. We conducted this prospective study to evaluate how HRV affects brain metastasis (BM) patients. Fifty-one BM patients who had not undergone previous brain operation or radiotherapy (RT) were recruited from January 2010 to July 2012, and 40 patients were included in the final analysis. A 5-minute electrocardiogram was obtained before whole brain radiotherapy. Time domain indices of HRV were compared with other clinical factors on overall survival (OS). In the univariate analysis, Karnofsky performance status (KPS) <70 (P = 0.002 ) and standard deviation of the normal-to-normal interval (SDNN) <10 ms (P = 0.004 ) significantly predict poor survival. The multivariate analysis revealed that KPS <70 and SDNN <10 ms were independent negative prognosticators for survival in BM patients with hazard ratios of 2.657 and 2.204, respectively. In conclusion, HRV is associated with survival and may be a novel prognostic factor for BM patients.